Primary hyperparathyroidism as an extremely rare cause of secondary myelofibrosis in childhood - Akyay, Arzu; Cihangiroglu, Gulcin; Ozkan, Yusuf; Deveci, Ugur; Bahceci, Semiha; Cetinkaya, Ziya (Walter de Gruyter Gmbh, 2013)
Primary hyperparathyroidism (PHP) and myelofibrosis are rare entities in childhood. Myelofibrosis secondary to PHP is also extremely rare. We report a 15-year-old boy presented with generalized weakness, vomiting, and pallor. A parathyroid adenoma was detected on the left distal parathyroid gland. PHP was diagnosed together with hepatosplenomegaly and pancytopenia. Bone marrow biopsy revealed grade 3-4 reticulin fibrosis. As early as 2 months after the left distal parathyroidectomy, hematologic parameters improved without any other intervention. His liver and spleen also gradually decreased in size. We concluded that the pancytopenia was as a result of myelofibrosis from PHP.
Keywords: childhood; myelofibrosis; primary hyperparathyroidism